Does initiating care in alternate care sites decrease time to disposition in the emergency department? - Alyssa Mangino; Lakshman Balaji; Bryan Stenson; Larry A. Nathanson; David Chiu; Shamai A. Grossman (Journal of the American College of Emergency Physicians Open)
Abstract Objectives During the coronavirus disease 2019 (COVID‐19) pandemic surge, alternate care sites (ACS) such as the waiting room or hospital lobby were created amongst hospitals nationwide to help alleviate emergency department (ED) overflow. Despite the end of the pandemic surge, many of these ACS remain functional given the burden of prolonged ED wait times, with providers now utilizing the waiting room or ACS to initiate care. Therefore, the objective of this study is to evaluate if initiating patient care in ACS helps to decrease time to disposition. Methods Retrospective data were collected on 61,869 patient encounters presenting to an academic medical center ED. Patients with an emergency severity index (ESI) of 1 were excluded. The “pre‐ACS” or control data consisted of 38,625 patient encounters from September 30, 2018 to October 1, 2019, prior to the development of ACS, in which the patient was seen by a physician after they were brought to an assigned ED room. The “post‐ACS” study cohort consisted of 23,244 patient encounters from September 30, 2022 to October 1, 2023, after the initiation of ACS, during which patients were initially seen by a provider in an ACS. ACS at this institution included the three following areas: waiting room, ambulance waiting area, and a newly constructed ACS that was built next to the ED entrance on the first floor of the hospital. The newly constructed ACS consisted of 16 care spaces each containing an upright exam chair with dividers between each care space. Door‐to‐disposition time (DTD) was calculated by identifying the time when the patient entered the ED and the time when disposition was decided (admission requested or patient discharged). Using regression analysis, we compared the two data sets to determine significant differences among DTD time. Results The largest proportion of encounters were among ESI 3 patients, that is, 56.1%. There was a significant increase in median DTD for ESI 2 and 3 patients who were seen initially in an ACS compared to those who were not seen until they were in an assigned ER room. Specifically, there was a median increase of 40.9 min for ESI 2 patients and 18.8 min for ESI 3 patients who were seen initially in an ACS (p < 0.001). There was a 29‐min decrease in median DTD for ESI 5 patients who were seen in ACS (p = 0.09). Conclusions Initiating patient care earlier in ACS did not appear to decrease DTD time for patients in the ED. Overall, the benefits of early initiation of care likely lie elsewhere within patient care and the ED throughput process.